Pengaruh Green Accounting, Enviromental Disclousure, Carbon Emissional Disclousure terhadap Kinerja Keuangan pada Perusahaan Manufaktur - Sinta Hidayatul Fatmawati; Dwi Ermayanti Susilo (Owner : Riset dan Jurnal Akuntansi, 2026)
This study is motivated by the increasing demand for environmental transparency and the importance of sustainability practices in improving corporate financial performance. The objective of this research is to examine the effect of green accounting, environmental disclosure, and environmental disclosure on financial performance with leverage as a control variable. This study offers a novel contribution by simultaneously integrating three environmental variables into a single empirical model and utilizing recent data from the basic materials and chemical manufacturing subsector for the 2022–2024 period. The population consists of 71 manufacturing companies listed on the Indonesia Stock Exchange, with 42 firms selected through purposive sampling, resulting in 126 observations. The analysis method employs panel data regression using the Random Effect Model (REM) with EViews software. The results indicate that green accounting and environmental disclosure have a significant positive effect on financial performance, while environmental disclosure shows no significant effect. Regarding the control variable, only environmental disclosure significantly affects leverage. Simultaneously, all independent variables significantly influence financial performance. The findings suggest that the effectiveness of sustainability practices in enhancing financial performance is contextual, emphasizing the importance of implementation quality rather than mere disclosure.